IMPROVING STUDENT WRITING SKILSS OF RECOUNT TEXT IN INSTAGRAM BY 8 GRADE STUDENT AT SMP 2 TABANAN - NI PUTU AYU KARTIKA SARI DEWI; NI GUSTI AYU PUTU DEVIK MIRA DIANTARI; I WAYAN MAWA; I MADE SUAMBA (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2025)
The potential of Instagram continues to show an increase in users from year to year. This article is motivated by the anxiety of using Instagram in improving recount text writing skills . However, not many lecturers utilise Instagram for learning in lectures. Therefore, this article has an urgency to examine the potential utilisation of Instagram in learning to write recount text. The purpose of this research is to explore various relevant studies and literature related to the topic. The method used is a Classhroom Action Research, using literature sources to find out the potential and use of the media. The result of this study is that the potential of Instagram in learning to write is huge. In addition, the use of Instagram in improving recount text writingskills has shown real results. The various features available in the media are very supportive for recount text.